2004
DOI: 10.1007/s12144-004-1020-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and sex role orientation on help-seeking attitudes

Abstract: This study investigated the effects of gender and sex role orientation (masculinity and femininity) on attitudes toward seeking professional psychological help in a sample of 163 student trainee teachers (52 males and 111 females) in Singapore. The mean age of students was 25.39 years (SD = 3.80). ANOVAs revealed statistically significant main effects for gender and femininity on attitudes toward help-seeking. Specifically, females were reported to have more positive overall attitudes toward professional help-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
64
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 38 publications
11
64
2
1
Order By: Relevance
“…There is limited published research on adolescent help-seeking behavior in Asia. To date, fewer than five studies on adolescent help-seeking attitudes and behavior based in Asia have been identified (Ang, Lim, Tan, & Yau, 2004;Fukuhara, 1986;Yeh, 2002). More empirical work is urgently needed to better understand Asian adolescents who seek professional help versus those who do not.…”
Section: A Study Of Help-seeking Behavior Among Secondary School Studmentioning
confidence: 99%
“…There is limited published research on adolescent help-seeking behavior in Asia. To date, fewer than five studies on adolescent help-seeking attitudes and behavior based in Asia have been identified (Ang, Lim, Tan, & Yau, 2004;Fukuhara, 1986;Yeh, 2002). More empirical work is urgently needed to better understand Asian adolescents who seek professional help versus those who do not.…”
Section: A Study Of Help-seeking Behavior Among Secondary School Studmentioning
confidence: 99%
“…Similarly, compared with men, women have been found to have more positive overall attitudes toward professional help-seeking, a greater willingness to recognize the need for help, and a greater tolerance for any societal stigma associated with help seeking (Ang, Lim, Tan, & Yau, 2004;Krogh, 2007). Hunt, Lewars, Emslie, and Batty (2007) reported that higher 'femininity' scores in men were associated with a lower risk of coronary heart disease death, while no such relationship was observed with the women in their study.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most consistent findings is that female individuals hold views and attitudes toward seeking psychological help that are more positive than those male individuals hold and use more psychological services (Addis & Mahalik, 2003;Ang, Lim, & Tan, 2004;Fischer & Farina, 1995;Fischer & Turner, 1970;Leong & Zachar, 1999;Morgan, Ness, & Robinson, 2003;Vogel & Wester, 2003). However, there are still contradictory results (Atkinson & Gim, 1989;Atkinson, Lowe, & Matthews, 1995;Dadfar & Friedlander, 1982;Masuda, Suzumura, Beauchamp, Howells, & Clay, 2005;Furnham & Andrew, 1996), showing no gender differences.…”
mentioning
confidence: 99%